Reproductive Toxicity of Nanomaterials Using Silver Nanoparticles and Drosophila as Models - Mohamed Alaraby; Doaa Abass; Javier Gutiérrez; Antonia Velázquez; Alba Hernández; Ricard Marcos (Molecules)
Reproductive toxicity is of special concern among the harmful effects induced by environmental pollutants; consequently, further studies on such a topic are required. To avoid the use of mammalians, lower eukaryotes like Drosophila are viable alternatives. This study addresses the gap in understanding the link between reproductive adverse outcomes and the presence of pollutants in reproductive organs by using Drosophila. Silver nanoparticles (AgNPs) were selected for their ease of internalization, detection, and widespread environmental presence. Both male and female flies were exposed to AgNPs (28 ± 4 nm, 100 and 400 µg/mL) for one week. Internalization and bioaccumulation of AgNPs in organs were assessed using transmission electron microscopy, confocal microscopy, and inductively coupled plasma mass spectrometry. Substantial accumulation of AgNPs in the gastrointestinal tract, Malpighian tubules, hemolymph, reproductive organs (ovaries and testes), and gametes were observed. The highest AgNP content was observed in testes. Exposure to AgNPs reduced ovary size and fecundity, though fertility and gender ratios of the offspring were unaffected. Significant deregulation of reproductive-related genes was observed, particularly in males. These findings underscore the utility of Drosophila as a model for evaluating reproductive hazards posed by AgNP exposure. The ease of AgNP internalization in Drosophila reproductive targets could be extrapolated to mammalians, raising concerns about the potential impacts of nanoparticle exposure on reproduction toxicity in humans.